2003
DOI: 10.1001/archinte.163.17.2066
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Identifiers of Complicated Staphylococcus aureus Bacteremia

Abstract: Readily available clinical variables can help identify patients at risk for complicated SAB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
441
4
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 577 publications
(473 citation statements)
references
References 55 publications
(63 reference statements)
22
441
4
6
Order By: Relevance
“…Fowler et al 7 proposed a prognostic model of complicated SAB using the predictors from their study; community acquisition of organisms, persistent bacteremia, persistent fever over 72 hours, and skin examination suggestive of an acute systemic infection. Muder et al 8 reported a relationship between SABU and subsequent SAB, but they did not examine the association between SABU and the risk of complicated SAB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fowler et al 7 proposed a prognostic model of complicated SAB using the predictors from their study; community acquisition of organisms, persistent bacteremia, persistent fever over 72 hours, and skin examination suggestive of an acute systemic infection. Muder et al 8 reported a relationship between SABU and subsequent SAB, but they did not examine the association between SABU and the risk of complicated SAB.…”
Section: Discussionmentioning
confidence: 99%
“…5 Risk stratification for these complications is a clinical challenge. Fowler et al 7 postulated some clinical identifiers of complicated SAB; however, predicting which patients will develop a complication from SAB remains very difficult. Muder et al 8 demonstrated that the presence of SA bacteriuria (SABU) correlates with subsequent SAB, but a possible association of SABU with complicated bacteremia was not examined.…”
mentioning
confidence: 99%
“…Producción de penicilinasas. Las bacteriemias por S. aureus presentaban tasas de mortalidad que se acercaban al 80%, y hasta el 70% desarrollaban metástasis infecciosas en la era preantibiótica (1,16,32). La introducción de las benzilpenicilinas al ámbito clínico en 1941, produjo una mejoría notable en el pronóstico de los pacientes, pero en 1942 se identificaron las primeras cepas de S. aureus resistentes a la penicilina.…”
Section: Mecanismos De Resistencia Antibiótica Del S Aureusunclassified
“…El SCCmec puede transportar en forma variable genes de resistencia a otros antibióticos como aminoglucósidos, clindamicina, eritromicina, rifampicina, tetraciclina y trimetoprimsulfametoxazol (16,(32)(33)(34); los SARM adquiridos en el hospital son los que presentan más comúnmente resistencia a estos antibióticos. La expresión fenotípica de estos perfiles de sensibilidad antibiótica se ha utilizado como una herramienta más para clasificar el origen de las cepas de SARM.…”
Section: Mecanismos De Resistencia Antibiótica Del S Aureusunclassified
See 1 more Smart Citation